BIL1-mediated MP phosphorylation integrates PXY and cytokinin signalling in secondary growth - Han, Soeun; Qi, Jiyan; Greb, Thomas (Nature plants, 2018)
The vascular cambium is a lateral meristem that is particularly active during secondary growth. Here, several signalling pathways (peptide, receptor, auxin and cytokinin) are linked together to explain how vascular development is regulated.